SUSTAINABLE DEVELOPMENT & DEMOCRACY IN INDIA A POLICY ANALYSIS FROM TRIPURA & WEST BENGAL - Sarkar, Partha Sarathi (International Journal of Research -GRANTHAALAYAH, 2024)
This research article delves into the intricate relationship between sustainable development and democracy, with a specific focus on the states of Tripura and West Bengal in India. Through a comprehensive policy analysis, it examines the extent to which democratic governance influences sustainable development initiatives in these regions. Tripura and West Bengal offer contrasting socio-political landscapes, making them ideal case studies to explore the interplay between democratic principles and sustainable development policies. By scrutinizing the implementation, effectiveness, and outcomes of various sustainability initiatives in both states, this study aims to identify key factors that either facilitate or hinder the integration of sustainable development goals within democratic frameworks. Furthermore, it evaluates the role of governmental institutions, civil society organizations, and grassroots movements in promoting sustainable development practices amidst democratic governance structures. The findings of this research contribute to a deeper understanding of how democracy can serve as a catalyst or a constraint in fostering sustainable development at the regional level, offering valuable insights for policymakers, development practitioners, and scholars alike.